2010
DOI: 10.1007/s00468-010-0460-7
|View full text |Cite
|
Sign up to set email alerts
|

Cambial growth dynamics and climatic control of different tree life forms in tropical mountain forest in Ethiopia

Abstract: Munessa Forest is a mountain forest in southeastern Ethiopia experiencing seasonal rainfall variation. We investigated seasonal cambial activity and dormancy from increment rates of four different tree species belonging to varying life forms, namely, evergreen native conifer (Podocarpus falcatus), evergreen introduced conifer (Pinus patula), evergreen broadleaved tree (Prunus africana) and deciduous broadleaved tree (Celtis africana). Measurements of stem radius fluctuations were registered with the help of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 33 publications
6
67
0
4
Order By: Relevance
“…3). This is consistent with the results of Huete et al (2006), which indicated a strong influence of radiation on leaf phenology, and previous ground-based studies in tropical forests which have highlight an exchange of leaves and a reduced wood production during drier months (O'Brien et al, 2008;Rice et al, 2004;Krepkowski et al, 2011). However, our results do not support a predominant role of radiation in forest productivity expressed as wood production (Fig.…”
Section: Wood Productionsupporting
confidence: 90%
“…3). This is consistent with the results of Huete et al (2006), which indicated a strong influence of radiation on leaf phenology, and previous ground-based studies in tropical forests which have highlight an exchange of leaves and a reduced wood production during drier months (O'Brien et al, 2008;Rice et al, 2004;Krepkowski et al, 2011). However, our results do not support a predominant role of radiation in forest productivity expressed as wood production (Fig.…”
Section: Wood Productionsupporting
confidence: 90%
“…In Sertânia, we assume that the plants used their accumulated water reserves to satisfy the demand for growth stimulated by photoperiod. For many deciduous species growth is only initiated after the sprouting of new leaves, as shown for Celtis africana in Ethiopia (KREPKOWSKI et al, 2011). Markesteijn et al (2010) also highlight the difference of tolerance and leaf phenology associated with soil water potential that suffers influence of temporal variation, mainly depending on the annual rainfall cycle and spatial variation that results from topography and vertical distribution of water in soil layers.…”
Section: Tenuiflora Grew At Least 44% More In the Open Areas With mentioning
confidence: 88%
“…Mais recentemente, análises do crescimento das árvores vêm sendo empregadas para compreensão das respostas das espécies diante das mudanças climáticas, ocasionadas por ações antrópicas ou naturais, na tentativa de prever alterações na estrutura florestal decorrentes dessas novas condições (CLARK et al, 2010;WAGNER et al, 2012). Assim, a avaliação do CCT do tronco das árvores pode ser uma forma de caracterizar a autoecologia das espécies e o funcionamento de florestas, contribuindo para o manejo adequado e o sucesso de reflorestamentos em cenários futuros (KREPKOWSKI et al, 2011). Adicionalmente, a avaliação da dinâmica de crescimento pode, também, determinar os ciclos de formação da madeira (CLARK et al, 2010;KREPKOWSKI et al, 2011) e, indiretamente, fornecer inferências sobre a atividade cambial e a formação dos anéis de crescimento das árvores, de forma a contribuir para estudos dendrocronológicos e dendroecológicos WIMMER, 2001;LISI et al, 2008).…”
Section: Introductionunclassified
“…Assim, a avaliação do CCT do tronco das árvores pode ser uma forma de caracterizar a autoecologia das espécies e o funcionamento de florestas, contribuindo para o manejo adequado e o sucesso de reflorestamentos em cenários futuros (KREPKOWSKI et al, 2011). Adicionalmente, a avaliação da dinâmica de crescimento pode, também, determinar os ciclos de formação da madeira (CLARK et al, 2010;KREPKOWSKI et al, 2011) e, indiretamente, fornecer inferências sobre a atividade cambial e a formação dos anéis de crescimento das árvores, de forma a contribuir para estudos dendrocronológicos e dendroecológicos WIMMER, 2001;LISI et al, 2008).…”
Section: Introductionunclassified